2018
DOI: 10.1017/s0022215118000749
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic gadolinium magnetic resonance imaging supports the role of endolymphatic hydrops in the pathogenesis of immune-mediated inner-ear disease

Abstract: This study confirms the presence of endolymphatic hydrops in immune-mediated inner-ear disease patients. The virtual absence of hydrops in patients with secondary immune-mediated inner-ear disease is remarkable, although firm conclusions cannot be drawn; this should be explored in a multicentre study with a larger sample of patients. A different immune reaction without development of endolymphatic hydrops should not be ruled out in secondary immune-mediated inner-ear disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…CMV infection, especially in congenital contexts, has been identified as among the most prevalent of the infective etiopathologies of SNHL, with deleterious consequences almost invariably for hearing and often too the vestibular system [6466]. Moreover, CMV has been suggested to lead to hydropic ear disease, and so too has EH been linked to immune-mediated inner-ear disease [67, 68]. So CMV is probably influential for a variety of pathophysiological processes of the vestibular and cochlear labyrinths that are themselves associated strongly with MD, and thus too in MD CMV-infection may be a factor in facilitating dysregulation of the inner-ear labyrinths, a hypothesis suggested by Arenberg and colleagues [48].…”
Section: Discussionmentioning
confidence: 99%
“…CMV infection, especially in congenital contexts, has been identified as among the most prevalent of the infective etiopathologies of SNHL, with deleterious consequences almost invariably for hearing and often too the vestibular system [6466]. Moreover, CMV has been suggested to lead to hydropic ear disease, and so too has EH been linked to immune-mediated inner-ear disease [67, 68]. So CMV is probably influential for a variety of pathophysiological processes of the vestibular and cochlear labyrinths that are themselves associated strongly with MD, and thus too in MD CMV-infection may be a factor in facilitating dysregulation of the inner-ear labyrinths, a hypothesis suggested by Arenberg and colleagues [48].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is typically obtained to rule out retrocochlear pathology 3 . Although there is no correlation between cochlear enhancement on MRI and proven AIED, MRI with intratympanic gadolinium may have utility in diagnosing AIED through detection of inner ear gadolinium 22,23 . If MRI is negative, work‐up should be continued with laboratory evaluation to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This system contains 28 "yes or no" questions across 5 sections: study quality (10), external validity (3), study bias (7), confounding and selection bias (6), and power of the study (1). Down and Black score ranges were then given corresponding quality levels: excellent (26)(27)(28), good (20)(21)(22)(23)(24)(25), fair (15)(16)(17)(18)(19), and poor (<15). The quality of each study included in this review was assessed using this checklist and is reported in Table 2.…”
Section: Bias Assessmentmentioning
confidence: 99%
“…Today, the relationship between ELH and MD symptoms (for review cp [3]), as well as the specificity of ELH for MD, has come under scrutiny. The underlying reason is that different ELH patterns can be found not only in MD [4,5], but also so far in 3.3-28% of healthy ears [6,7], various inner ear [8][9][10] and central [11][12][13][14] pathologies, as well as in anatomic or vascular abnormalities affecting endolymph resorption [15][16][17].…”
Section: Introductionmentioning
confidence: 99%